A Conversation with a Regulator : Meeting with Paul Boyle, Chief Executive of the Financial Reporting Council - Bender, Ruth (Cranfield University, 2009)
Prepared for the Audit Committee Chair Forum, published by Ernst & Young, CBI and Cranfield School of Management. This paper reflects the discussions at a meeting of the Audit Committee Chair Forum (ACCF) held on 19th March 2009, which was addressed by Mr Paul Boyle, Chief Executive of the Financial Reporting Council. The meeting discussed corporate governance and corporate reporting in the UK.